Teaching the “Other Law” in a South African University: Some Problems Encountered and Possible Solutions - M Maithufi (In Memory); CA Maimela (Obiter, 2020)
African customary law is a legal system that is recognised in South Africa and forms part of the law of the indigenous people of South Africa. Due to colonialism and apartheid, this legal system was rejected and underdeveloped in favour of common law. The supremacy of the Constitution and its recognition of African customary law as an independent legal system, separate from the common law, aimed to correct past injustices that flowed from the underdevelopment of this important legal system. Whether the Constitution and higher learning institutions have attained the goal of developing African customary law in South Africa is a question that will be explored and debated in this contribution. Its aim is to assess the role of higher learning institutions in developing African customary law through their teaching of this system of law, as well as to outline some of the challenges faced by these institutions in offering an African customary law course to students. Possible solutions are discussed; the aim is to ensure that the teaching component of African customary law is developed, and to contribute to the current debate about curriculum transformation among universities and various stakeholders in higher learning. Curriculum transformation is key to the future development and inclusiveness of the South African community that is so diverse.